Differences in Plasma Cytokine Levels between Elite Kayakers and Nonathletes. (27th May 2013) - Borges, G. F.; Rama, L.; Pedreiro, S.; Alves, F.; Santos, A.; Massart, A.; Paiva, A.; Teixeira, A. M.
Abstract : Regular moderate exercise has been shown to have anti-inflammatory effects that help prevent several chronic diseases. However, the effects of chronic training an elite athletes have not been the focus of much research. This study aimed to determine whether there were differences in cytokine levels (IL-1 β, IL-1ra, IL-6, IL-10, IL-18, IFN- γ, and TNF- α ) in circulating peripheral blood (PB) between elite kayakers and nonathletes. Subjects were 13 elite male kayakers, aged 20.0 ± 3 years, with average body mass of 75.0 ± 7.9 kg and 177.3 ± 7.1 cm height and with a VO 2 max of 58.3 ± 7.8 mL·kg −1 ·min −1 . The nonathletes were 7 men, aged 18.2 ± 1.1 years, body mass of 81.3 ± 13.8 kg, and 171.9 ± 4.5 cm height. Blood samples were collected after six weeks of offtraining and before the start of a new training season. PB leukocyte populations were determined by flow cytometry. Cytokine levels were quantified by ELISA. When nonathletes were compared with the kayakers, the latter exhibited lower plasma concentrations of IL-1 β, IL-18, and IFN- γ as well as a lower concentration of IL-1ra. Positive correlations between IL-18 and B cells in the athletes were also found. These results seem to reinforce the anti-inflammatory role of regular training.